COMPARATIVE ANALYSIS OF CALCULATION METHODS OF PILE FOUNDATIONS UNDER THE STATIC AND DYNAMIC LOADS - Petrenko, V. D.; Tiutkin, O. L.; Stoicheva, M. B. (Science and Transport Progress, 2007)
In the article the comparative analysis of calculation methods of pile foundations at the static and dynamic loadings s represented, the features of dynamic calculation of such type of constructions are analyzed.